Pendampingan Sertifikasi Halal Produk Makanan Usaha Mikro dan Kecil Melalui Website SIHALAL - Setyowati, Ratna Dewi; Cahyani, Putri Gita; Annisa, Nurul; Ulya, Husna Ni’matul (Ngarsa: Journal of Dedication Based on Local Wisdom, 2024)
Understanding halal products in the digital era makes people smarter in choosing the products they want to buy. The importance of a product having halal certification will make it a branding tool in itself so that it will generate public trust in using the product. Bekare Village, Bungkal District, Ponorogo Regency, has many micro and small businesses as one of the community's jobs besides being farmers. However, they do not yet realize the importance of having protection tools that have been established by law, such as halal certification. The aim of this service is to provide an understanding of halal certification and help people obtain halal certificates. This service uses the service-learning method, namely applying the knowledge possessed by students and lecturers to the local community. This service succeeded in transforming the knowledge of the Bekare Village community regarding halal certification. They originally had the principle that the important thing was to sell the product and get their capital back. Currently they realize the importance of halal certificates for marketing and developing their business products. This service also succeeded in facilitating four micro and small businesses in obtaining halal certificates from the Ministry of Religious Affairs. Keywords: Assistance with halal certification, Self declare, Food products, Micro and Small Enterprises Abstrak: Pemahaman produk halal di era yang serba digital menjadikan masyarakat semakin pandai memilih produk yang akan dibelinya. Pentingnya suatu produk yang memiliki sertifikasi halal akan menjadikan alat branding tersendiri sehingga akan menghasilkan kepercayaan masyarakat dalam menggunakan produk tersebut. Desa Bekare, Kecamatan Bungkal, Kabupaten Ponorogo, memiliki banyak usaha mikro dan kecil sebagai salah satu pekerjaan masyarakat di samping sebagai petani. Namun, mereka belum menyadari pentingnya memiliki alat perlindungan yang telah ditetapkan UU seperti sertifikasi halal. Tujuan pengabdian ini adalah untuk memberi pemahaman tentang sertifikasi halal dan membantu masyarakat memperoleh sertifikat halal. Pengabdian ini menggunakan metode service-learning yaitu menerapkan pengetahuan yang dimiliki para mahasiswa dan dosen kepada masyarakat setempat. Pengabdian ini berhasil mentransformasi pengetahuan masyarakat Desa Bekare mengenai sertifikasi halal. Mereka semula berprinsip bahwa yang penting produk terjual habis dan memperoleh modal kembali. Saat ini mereka menyadari pentingnya sertifikat halal bagi pemasaran dan pengembangan produk-produk usaha mereka. Pengabdian ini juga berhasil menfasilitasi empat usaha mikro dan kecil dalam memperoleh sertifikat halal dari Kementerian Agama. Kata kunci: Pendampingan sertifikasi halal, Self declare, Produk makanan, Usaha Mikro dan Kecil